(untitled) (Journal Of Educational and Psychological Researches, 2015)
Undesirable behaviors among students are consider one of the danger problems threating societies and educational and scientific institutions of countries because its one of the way to express aggression , so the instructors consider one of the most important people could be trust their evaluation and logical view , therefore the present research aimed to : • Recognize undesirable behavior in students of University by the view of their instructors • Measure the level of undesirable behavior in students of university by the view of their instructors • Recognize more common undesirable behavior in students of University by the view of their instructors • Recognize undesirable behavior in students of University according to , range and percentage • The researcher built scale of undesirable behavior in students of University by the view of their instructors contains from (33) items distributing on three Field (verbal behaviors, motion and group behaviors, the results appears : • the mean sample was (102) degree is higher than hypothetical mean which was (82.5) degree is significantly effect in (5 %) • the most common behaviors are , agreement of group absence , postpone the exam for un logical excuse . while the less common behaviors was , laughing without real reason in class , discussion without respect • undesirable behavior in students of University by the view of their instructors contains underline second level (high) with (54 – 74 ) range because of (32) frequency ratio at 51 % . According to results ,the researcher concluded with recommendations and suggestions